2006
DOI: 10.1097/01.gim.0000237781.10594.d1
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular bases of hearing loss in multi-systemic mitochondrial cytopathy

Abstract: Purpose: Hearing loss is a common clinical feature in classic mitochondrial syndromes. The purpose of this study was to evaluate the diverse molecular etiologies and natural history of hearing loss in multi-systemic mitochondrial cytopathies and the possible correlation between degree of hearing loss and neurological phenotype. Methods: In this retrospective study we evaluated the clinical features and molecular bases of hearing loss associated with multi-systemic mitochondrial cytopathy. Forty-five patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Non-syndromic SNHL associated with mtDNA mutations is generally progressive (4,5), involving mainly higher frequencies (68) and is generally symmetric HL. The onset of HL usually occurs in childhood, is predominantly post-lingual and may be accompanied with vertigo (9) and tinnitus (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Non-syndromic SNHL associated with mtDNA mutations is generally progressive (4,5), involving mainly higher frequencies (68) and is generally symmetric HL. The onset of HL usually occurs in childhood, is predominantly post-lingual and may be accompanied with vertigo (9) and tinnitus (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the hearing loss associated with mitochondrial disorders has been characterized as a high-frequency, progressive, sensorineural loss [11][12][13]. There have also been some reports of sensorineural loss affecting all frequencies equally.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, mitochondrial abnormalities can lead to multisystem disorders such as the mitochondrial encephalomyopathies: Kearns-Sayre syndrome (KSS) [5]; mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episode (MELAS) [6]; and myoclonic epilepsy associated with ragged-red fibers (MERRF) [7], all of which may include sensorineural hearing loss (often progressive) as a symptom [8][9][10]. Hearing loss associated with mtDNA mutations has been characterized as a progressive, sensorineural hearing loss across higher frequencies or across all frequencies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It may be of cochlear origin or be caused by an auditory neuropathy. One study suggested that 40% of individuals with mitochondrial disease have hearing loss [72]. The most frequent genetic variant predisposing to mitochondrial nonsyndromic SNHL is m.1555A>G in the MT‐RNR gene encoding a mitochondrial rRNA.…”
Section: Other Phenotypes: a Systems Approach To Mitochondrial Diseasmentioning
confidence: 99%